Enhanced mixed proton and electron conductor at room temperature from chemically modified single-wall carbon nanotubes. Issue 14 (18th March 2022) - Rabin, Nurun Nahar; Islam, Md. Saidul; Fukuda, Masahiro; Yagyu, Junya; Tagawa, Ryuta; Sekine, Yoshihiro; Hayami, Shinya
Abstract : A chemically modified single-wall carbon nanotube showing efficient mixed proton and electron conduction at room temperature is demonstrated. Abstract : Remarkably high mixed proton and electron conduction arising from oxidized single-wall carbon nanotubes at room temperature is demonstrated. The respective proton and electronic conductivities are 1.40 and 8.0 × 10 −2 S cm −1 in the in-plane direction, and 3.1 × 10 −2 and 1.1 × 10 −3 S cm −1 in the out-of-plane direction, indicating their potential in a wide range of solid electrolyte membranes.